Automatic Control System for Pressure Tank Testing According to TIS 1252-2537 - Chaivisetsakul, Supakchai; Janthong, Manusak; Yamfang, Manop; Preamjai, Nopporn; Thepha, Sirichai; Pramot, Pipat (Frontiers in Engineering Innovation Research, 2021)
This research is to develop a test kit for air pressure tanks for regular manual control, to achieve higher efficiency by reducing work steps in the traditional experiment and more accurate. The researcher studied the design of the automatic control system for testing 64-liter capsule-shaped pressure tanks by using the test kit for air pressure storage to test the pressure by using the Hydrostatic Pressure method and using a PI controller and setting the parameters on the program LabVIEW to control the system. Adjust the proportional growth rate variable Kc and the expansion rate of integral Ki to 13 and 1.308, respectively. The signal output is then amplified to control the solenoid valve using PWM (Pulse Width Modulation). By comparing the traditional manual control methods to the PI controller, the results showed that the PI controller better responds to a set point of a constant pressure state at 13 bar. The average error is lower than 1.71 percent compared to the traditional manual control method, with an average error of about 1.75 percentage